Influência da socialização organizacional percebida sobre o comprometimento organizacional : um estudo de caso na Polícia Militar de Sergipe - Marques, Erika Cavalcanti (2013)
This study is about two psychological phenomenons which occur in the organizations: organizational socialization and organizational commitment. Based on literature, was considered the organizational socialization as a socio-historic process based in the organizational culture. It is continuous and occurs with the relationship of the employees with partners, boss and clients/users of the organization, being operationalized by the organizational activities and the proactive of the employees to their own socialization. The organization commitment, in general, considered as a tie among the employee and the organization, contributes to explain why the employee continues at the organization. Here is treat as a tridimensional construct as: Affective (affect and attachment to the organization), instrumental (employee calculate the benefits and costs about go away from the organization and if there are perspective to be absorbed by other organizations) and normative (to adhere to the organizational norms and issues as an obligation). By the way, the present study has as objective to analyze the organizational socialization influence on the organizational commitment of employees, in four specialized bases of the Sergipe.s State Military Police, expecting find a positive relation between both phenomenons, because, theoretically, there is a sense that a very well socializated employee develops organizational commitment. The methodology consisted in the collective administration of the Inventario de Socializacao Organizacional (ISO), Escala de Comprometimento Organizacional and a formulary of social and demographics data in a sample of 270 polices. In major, the sample characterized by soldiers and capes, in media with 15,22 years old of organization, male, in media with 37 years old, with complete or incomplete college, married, two sons, in media with R$ 4.020,40 of remuneration, developing operational activities. By exploratory factorial analyze of the ISO, resulted in a factorial structure, with three factors (KMO=0,83; r2=33,12%): F1.Organizational integration-IORG-(seven items, r2=23,01%, ¥á=0,74); F2. Procedures and activities domino-DPA-(nine items, r2=5,38%, ¥á=0,78); F3.Proactive and Competency-P&C-(eight items, r2=4,73%, ¥á=0,78). It resulted in preponderance of the DPA Factor (M=4,17) in comparison to the others. About the commitment, the results presented an excellent reliability degree to the scale selected, and about the middle score of the respondents, in each dimension of commitment, they denoted low affective and instrumental commitment and non normative commitment perception. The multiple regression analyze presented, as affective commitment prediction variables, the IORG and P&C factors, followed by time in the function and individual remuneration [F(4,233)=45,46; p<0,001], with 44% of explained variance. In this case, the distinction was the IORG. About the instrumental dimension, no one of the organizational socialization factors contributed to the explanation. About the normative base, resulted as predictors: years old variable, followed by IORG and P&C, time in the function [F(4,233)=17,70; p<0,001]. In this group the percentage of explained variance was low (23%). We concluded that the organizational socialization have influence on the organizational commitment because two organization socialization.s factors (IORG and P&C) explain at least two organizational commitment dimensions (affective and normative). This study contributes to think about the importance of the organizational strategies to socialize new employees, and the incentive to the employees. pro-activity in this process. A well succeeded process of integration of new employees contributes to the organizational commitment and its consequences (work satisfaction, absenteeism and turnover index, as example). These are aspects so desired by the organizations.